Exploring of the transesterification of castor oil to produce biodiesel using quicklime as a basic catalyst - Fatin ‘Atikah, Abd. Manan (2013)
This research is basically an experiment to exploring the transesterification of Castor oil to biodiesel using quicklime (CaO) as solid base catalyst. The objectives of this research are to use heterogeneous catalyst quicklime for possible high yield production biodiesel from castor oil. In this research, castor oil has been chosen as feedstock because it is readily available in Malaysia and non-edible oil. Methanol was chosen as alcohol solvent because its price is cheaper compare to other type of alcohol. Through a process called transesterification, biodiesel is made by reacting triglycerides (castor oil) with alcohol (methanol) in the presence of a catalyst (quicklime) to produce fatty acid methyl esters (biodiesel) and glycerol (co-product). This experiment was conducted with two different parameters which are methanol: oil ratio (3:1 and 4:1) and reaction time (60 minutes, 120 minutes and 180 minutes). The catalyst concentration was fixed at 1 wt% and the temperature was fixed at 60oC. The sample of each experiment was analysed using Gas Chromatography Mass Spectrometry (GC-MS). The best yield biodiesel product was 82% at reaction conditions; 3:1 methanol/oil ratio, 180 minutes, 1 wt% of CaO and 60oC.